Strength and Perceived Effort in Repetitive Upper-Limb Tasks: An OCRA Method Analysis of 900 Workers - Gobbo, Stefano; Bullo, Valentina; Favro, Francesco; Pavan, Davide; Doro, Beatrice; Bortoletto, Alessandro; De Palma, Giuseppe; Sala, Emma; Mattioli, Stefano; Di Blasio, Andrea; Bergamin, Marco (La Medicina del Lavoro, 2025)
Background: Work-related musculoskeletal disorders pose a significant burden on the population. The OCRA method plays a key role in assessing the risk associated with repetitive actions of the upper limbs. In this method, muscular force is evaluated based on the rate of perceived effort (RPE) reported by the worker, which can introduce subjective bias into the assessment. This study aims to determine whether testing the worker’s handgrip strength can improve the accuracy of the force assessment in the OCRA method. Methods: Handgrip strength was measured during the risk assessment process following the OCRA method. Data were divided into specific percentile ranks based on age, gender, height, and handedness. Results: 903 workers from 43 different Italian companies were surveyed. There was a significant difference in handgrip strength percentiles stratified by report of an RPE > 2 and those without (p = 0.047). Additionally, significant differences were found in perceived effort rates (based on the OCRA method) among workers with different levels of stratified handgrip strength (dominant hand: p = 0.04, non-dominant hand: p = 0.02). Conclusions: Workers performing repetitive upper limb actions at various strength levels experience different perceived effort rates during tasks. These findings suggest that measuring handgrip strength is a crucial component of risk assessments using the OCRA method. To date, this study’s sample size is among the largest for this evaluation method; we believe these results could be a significant step forward in improving the risk assessment process for biomechanical overload